SIRT1 modulation and lipid profile alterations in the cellular regulation of blood lipids in renal disorders among extremely obese individuals: SIRT1 and lipid profile in obese renal disease - Azeez , Zain Alabdean; Chabchoub , Elyes (Cellular and Molecular Biology, 2025)
The global epidemic of overweight and obesity is closely linked to the development of chronic kidney disease (CKD), with extremely obese individuals facing a particularly high risk. This study aimed to assess the relationship between lipid profile levels, SIRT1 expression, and RNA-34a-5P in the regulation of blood lipid levels among severely obese individuals with renal diseases. Conducted over six months in three specialized hospitals, the study included 100 participants divided into two groups: 50 obese individuals with renal diseases and 50 obese controls without renal problems. Ethical standards, including confidentiality and informed consent, were strictly observed. Biochemical assessments included measurements of total cholesterol, LDL, HDL, triglycerides, creatinine, GFR, SIRT1 protein (via Western blotting), and RNA-34a-5P expression (via qPCR). Statistical analysis was performed using SPSS v26 and Pearson's correlation. The results revealed a negative association between RNA-34a-5P expression and total cholesterol, LDL, triglycerides, and SIRT1 expression, while a positive but non-significant association was found with HDL and GFR. Notably, SIRT1 expression was significantly downregulated in the patient group compared to controls. These findings provide compelling evidence that SIRT1 expression is markedly reduced in extremely obese individuals with renal diseases, suggesting a potential molecular link between SIRT1, lipid metabolism, and renal dysfunction in severe obesity.